Natural resources and sustainable development : international economic law perspectives - Tan, Celine; Faúndez, Julio (Edward Elgar Publishing, 2017)
The centrality of natural resources to global economic growth has placed the debate over their ownership and control at the forefront of legal, territorial and political disputes. Combining both legal and policy expertise with academic and practitioner perspectives this book considers the dimensions of natural resource governance at a time when disputes over their use grow more acute. Focusing on the law, regulation and governance of natural resources, this timely work examines in detail the conflicts and contradictions arising at the intersection between international economic law, sustainable development and other areas of international law, most notably human rights law and environmental law. Exploring the views of different stakeholder groups in the natural resources sectors, key chapters consider whether their differing interests and concerns are adequately addressed under national and international law. This book will appeal to scholars of law, political science and development studies. It will also benefit policy practitioners and advocacy specialists in development NGOs, research institutes and international organisations.